Pengaruh Media Audiovisual Berbasis Video Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA Kelas IV SDN Kutajaya I Kabupaten Tangerang - Tirta Dianti (CV. Alim's Publishing, 2023)
In class IV SDN Kutajaya I science, the purpose of this study is to ascertain the impact of using audiovisual medium on student learning outcomes. A quasi-experimental research design was adopted for this investigation. All 124 fourth graders at SDN Kutajaya I were the population subjects for this study. Two classes of 62 kids were chosen as samples: class IV A, which served as the experimental class, and class IV B, which served as the control class. A multiple-choice test with 25 questions is used in the data collection process. A multiple-choice instrument with 25 trustworthy questions is used in the data gathering process. To test the pretest hypothesis in this study used the t test, from the results of the t test obtained control tcount = -1.12929 with a significant level of 95% (α = 0.05) obtained ttable = 2.0002 because -1.12929 < 2, 0002 (tcount < ttable) then H0 is accepted. As a result, there is no early learning difference between the experimental class and the control class in terms of student learning outcomes. The outcomes of a t test used to assess hypotheses at the conclusion of learning (posttest) in the experimental class and control class were tcalculate = 6.10834768 with a 95% confidence interval for significance ( = 0.05). obtained ttable = 2.0002 and H0 was rejected because 6.10834768 > 2.0002 (tcalculate > ttable). As a result, at the conclusion of the learning process, the experimental class and the control class had different student learning outcomes.